PERUBAHAN PIDANA DARI KUHP LAMA KE BARU SALAH SATU ADALAH REFORMASI PENEGAKAN HUKUM - M. Yusuf DM; Boby Putra Ramadhan Sebayang; Zulkarnaini; Ridho Wira Turnip; Herman Saputra (LPPM STIH Awang Long, 2025)
Criminal law reform in Indonesia marks a significant shift from the old Penal Code (KUHP) to the new KUHP, aimed at strengthening law enforcement, ensuring legal certainty, and protecting human rights (HR). This reform reflects the necessity of a modern criminal justice system that is responsive to democratic demands and oriented towards substantive justice. One of the main aspects of the reform is the emphasis on progressive legal principles, including the protection of human rights during law enforcement processes and recognition of victims' rights. The new KUHP introduces more diversified punishment mechanisms, alternative criminal resolutions, and clearer provisions regarding criminal liability, including for corporate crimes. The reform underscores the importance of balancing state interests with individual protection within the criminal justice system. Thus, law enforcement focuses not only on repressive aspects but also on preventive, restorative, and rehabilitative measures. This study highlights the transformation of criminal norms, changes in legal structures, and the practical impact of the new KUHP on law enforcement practices in Indonesia. The analysis employs normative and descriptive juridical approaches, examining amended, deleted, or added articles and their implications for criminal justice institutions, including the police, prosecutors, courts, and correctional facilities. The results indicate that KUHP reform not only updates legal norms but also shifts the paradigm of law enforcement towards a more humane and democratic approach. Implementation challenges, such as law enforcement capacity, public awareness, and harmonization with other regulations, are crucial factors determining the effectiveness of this reform. In conclusion, the new KUHP represents a significant milestone in establishing a fair, transparent criminal law system oriented towards human rights protection, while simultaneously strengthening the legitimacy of law enforcement in Indonesia.